AR/VR Teaching-Learning Experiences in Higher Education Institutions (HEI): A Systematic Literature Review - Belen Bermejo; Carlos Juiz; David Cortes; Jeroen Oskam; Teemu Moilanen; Jouko Loijas; Praneschen Govender; Jennifer Hussey; Alexander Lennart Schmidt; Ralf Burbach; Daniel King; Colin O'Connor; et al. (Informatics, 2023)
During the last few years, learning techniques have changed, both in basic education and in higher education. This change has been accompanied by new technologies such as Augmented Reality (AR) and Virtual Reality (AR). The combination of these technologies in education has allowed a greater immersion, positively affecting the learning and teaching processes. In addition, since the COVID-19 pandemic, this trend has been growing due to the diversity of the different fields of application of these technologies, such as heterogeneity in their combination and their different experiences. It is necessary to review the state of the art to determine the effectiveness of the application of these technologies in the field of university higher education. In the present paper, this aim is achieved by performing a systematic literature review from 2012 to 2022. A total of 129 papers were analyzed. Studies in our review concluded that the application of AR/VR improves learning immersion, especially in hospitality, medicine, and science studies. However, there are also negative effects of using these technologies, such as visual exhaustion and mental fatigue.